(untitled) (Research, Society and Development, 2020)
Objective: to analyze the scientific evidence about the socioeconomic factors associated with the occurrence of pregnancy in adolescence. Methods: consists of an integrative literature review carried out in the databases of the Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), at Banco de Dados em Enfermagem (BDENF) and at the Virtual Library Scientific Eletronic Library Online (SciELO). Were determined as descriptors: Pregnancy in Adolescence, Health, Education and Socioeconomic Factors. Data collection was carried out on August 29 of 2020, when all articles were selected and read in full. A form composed of previously determined variables was used to facilitate the compilation of information and the categorization of the studies. Results: 16 articles were selected in total, adding all the databases. Low educational level was the main socioeconomic factor found that predisposes to teenage pregnancy. Conclusion: became evident that teenage pregnancy is a phenomenon of social representation, with a higher incidence in social classes of low socioeconomic level.